2022
DOI: 10.2174/1574893617666220609114052
|View full text |Cite
|
Sign up to set email alerts
|

NeuMF: Predicting Anti-cancer Drug Response Through a Neural Matrix Factorization Model

Abstract: Background: Anti-cancer drug response has been urgently required for individualized therapy. Measurements with wet experiments are costly and time-consuming. Artificial intelligence-based models are currently available for predicting drug response but still have challenges in prediction accuracy. Objective: Construct a model to predict drug response values for unknown cell lines and analyze drug potential association properties in sparse data. Methods: Propose a neural matrix factorization (NeuMF) framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It has been shown that a deep neural network can generate better representations of arbitrary nonlinear relations among input entries and outperforms single-layer structures [34]. Through the deep neural network structure, the nonlinear and linear terms are approximately expressed as ( 9) and (10), respectively. f ðdÞ ¼ s ðLþ1Þ ðW ðLÞ c s ðLÞ ðW ðLÞ c ð� � � s ð1Þ ðW ð1Þ…”
Section: Model Structurementioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that a deep neural network can generate better representations of arbitrary nonlinear relations among input entries and outperforms single-layer structures [34]. Through the deep neural network structure, the nonlinear and linear terms are approximately expressed as ( 9) and (10), respectively. f ðdÞ ¼ s ðLþ1Þ ðW ðLÞ c s ðLÞ ðW ðLÞ c ð� � � s ð1Þ ðW ð1Þ…”
Section: Model Structurementioning
confidence: 99%
“…By solving (6), the optimized f(�), C and D can be achieved. Thus, based on (10), C is approximated by the product of the linear hidden layer weights. In a broad sense, C also represents the latent factor matrix of cell line learned in the DBDNMF.…”
Section: Model Structurementioning
confidence: 99%
See 2 more Smart Citations